Green Synthesis of Metal Nanoparticles via Natural Extracts: The Biogenic Nanoparticle Corona and Its Effects on Reactivity - Colavita, Paula (My University, 2015)
The optical and catalytic properties of metal nanoparticles have attracted significant attention for applications in a wide variety of fields, thus prompting interest in developing sustainable synthetic strategies that leverage the redox properties of natural compounds or extracts. Here, we investigate the surface chemistry of nanoparticles synthesized using coffee as a biogenic reductant. Building on our previously developed synthetic protocols for the preparation of silver and palladium nanoparticle/carbon composite microspheres a combination of thermogravimetric and spectroscopic methods were used to characterize the carbon microsphere and nanoparticle surfaces. Infrared reflectance spectroscopy and single particle surface enhanced Raman spectroscopy were used to characterize Pd and Ag metal surfaces, respectively, following synthesis. Strongly adsorbed organic layers were found to be present at metal nanoparticle surfaces after synthesis. The catalytic activity of Pd nanoparticles in hydrogenation reactions were leveraged to study the availability of surface sites, and coffee-synthesized nanomaterials were compared to commercial Pd-based hydrogenation catalysts. Our results demonstrate that biogenic adsorbates block catalytic surface sites and affect nanoparticle functionality. These findings highlight the need for careful analysis of surface chemistry as it relates to the specific applications of nanomaterials produced using greener or more sustainable methods.
PUBLISHED
Keywords: metal nanoparticles; metal nanoparticles